Quality in Postoperative Patient Handover: Different Perceptions of Quality Between Transferring and Receiving Nurses. Issue 1 (January 2019) - Reine, Elizabeth; Ræder, Johan; Manser, Tanja; Småstuen, Milada C.; Rust⊘en, Tone
Abstract : Background: A safe and efficient patient handover is important to ensure high-quality patient care and reduce the risk of patient harm. Few studies have explored handover activities beyond information transfer. Purpose: The aims were to assess overall postoperative handover quality and relate quality assessments to handover circumstances, conduct, and teamwork and to compare transferring and receiving nurses' evaluations of handover quality. Method: This was a cross-sectional study using the Norwegian Handover Quality Rating Form (N-HQRF). In addition, data were collected on nurses' evaluations of the patient condition, handover preparation, and participating nurses' clinical experience. Results: Although total perceived handover quality was high in a large majority of cases, there were significant differences between transferring and receiving nurses' evaluations of the same handover. Lower-quality handovers had a higher frequency of time pressure, uncertainty, and patient-related problems. Conclusion: The findings point to the need to assess handover quality in a wider perspective. Handover circumstances might impact handover quality and should be considered when procedures for handover quality are designed and implemented. Abstract : Supplemental Digital Content is Available in the Text.